Climate and Health: Extreme Events, Food Systems, and Nutrition - Venkat, Aishwarya. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Agriculture, Food and Environment.; Advisor: Elena Naumova.; Committee: Erin Coughlan De Perez, and William Masters.; Keywords: Climate change, Public health, and Economics.